Debating Calvinism : five points, two views - Hunt, Dave; White, James Robert, 1962- (Sisters, OR Multnomah, 2004)
Contents : Calvinism Affirmed : God's eternal decree -- Man's inability -- Unconditional election -- Jesus teaches the doctrines of Grace --- The golden chain of redemption -- Particular redemption: true atonement,true substitution -- Irresistable Grace: God saves without fail. Calvinism Denied : Calvin and Augustine: two Jonahs who sink the ship -- The central issue: God's love and character -- Regeneration before faith and salvation? -- Turning the Bible into a charade -- God's sovereignty and man's will -- Salvation offered to all -- Biblical assurance of Salvation.
Keywords: Calvinism; Reformed church -- doctrines